PERSONNEL INFORMATION SYSTEM RELATED TO THE ROLE OF ASN COMPETENCIES, WORK ENVIRONMENT, WORK MOTIVATION IN INCREASING WORK PRODUCTIVITY - Kamal, Fahmi -; Saddewisasi, Wyati; Fitri, Sri Adella Fitri Adella; Judijanto, Loso; Wahyudin, Wahyudin (Universitas Dharma Wacana, 2023)
Human resource is the executor of the various activities in an organization and have a very large role for the development of the organization. A organization has their own criteria in determining human resource qualification. The basic problem in the East Lombok Regency Health Office is how to spur employee performance to always improve. Excellent employees will contribute significantly to achieve the institution goals. This study aims to analyze and examine the factors influencing work productivity at the Health Office in East Lombok Regency. These factors include ASN competence, work environment and Â work motivation. The research used the quantitative with regression analysis method. The data was collected using questionnaires distributed to all employess of Health Office. The sampling method used is census sampling technique with a total population of 35 employees. The data were analysed with IBM SPSS version 22 and analysis was carried out by several tests such as validity test, realibility test, classic assumption, linear regression analysis and coefficient of determination test. The results of this study indicate that the partially, ASN competence, work environment and work motivation have a positive and significant effect on work productivity. Simultaneously, ASN competence, work environment and work motivation have a positive and significant effect on work productivity at the Health Office in East Lombok Regency. The findings can be reference for government in the regency area in order to improve employee performance that has a good impact on the quality of public services to the citizens.